The Role of HE4 in the Follow-Up of Advanced Ovarian, Fallopian Tube, and Primary Peritoneal Cancer-CEEGOG OX-01 Study - Presl, Jiri; Havelka, Pavel; Weinberger, Vit; Ovesna, Petra; Fekete, Peter; Fruhauf, Filip; Jedryka, Marcin; Bystricky, Branislav; Strojna, Aleksandra; Volodko, Nataliya; Matylevich, Olga; Herboltova, Petra; et al. (Cancers, 2024)
Background: Ovarian, fallopian tube, and primary peritoneal cancers often share clinical characteristics and are typically diagnosed at advanced stages due to nonspecific symptoms. The utility of tumor markers, particularly CA125 and HE4, in the diagnosis and follow-up of these cancers remains an area of active investigation. Objectives: The CEEGOG (Central and Eastern European Gynecologic Oncology Group) OX-01 study aimed to evaluate HE4's role alongside CA125 in follow-up for advanced-stage ovarian, fallopian tube, and primary peritoneal cancers. It assessed the potential for detecting recurrence using marker elevation and imaging methods, examining the necessity of dynamic monitoring and current cut-off values' accuracy for early relapse detection. Methods: In this multicenter prospective cohort study, 117 eligible patients with Stage III-IV cancers were included. Patients had elevated CA125 or HE4 at diagnosis and achieved complete remission after first-line treatment. HE4 and CA125 levels were monitored every 3-4 months in the first two years and every six months thereafter. CT scans were performed if markers exceeded set thresholds or increased by over 20%. Results: During a median follow-up of 13.7 months, 73% of patients relapsed. Median HE4 levels were significantly higher in relapsed patients. A 10 IU/mL increase from baseline in CA125 had a sensitivity of 83% and specificity of 93%, while a 15 pmol/L increase in HE4 had a sensitivity of 74% and specificity of 92% for predicting relapse up to three months before CT scan detection. Conclusions: The study found that dynamic changes in HE4 and CA125 levels, rather than predefined cut-off values, are crucial for early relapse detection. These markers may offer a significant lead time over imaging, potentially enabling earlier intervention. Further research is needed to validate these findings.
Keywords: HE4; tumor markers; CA125; recurrence detection; ovarian cancer